Climate change in Nepal – shall we wait until bitter consequences? - Lohani, Sunit N (Journal of Agriculture and Environment, 2007)
Although Nepal does not emit much of green house gas as compared to developed and industrialized economies, it has been facing several consequences of climate changes. Such changes are raising temperatures in the country’s sky too. Exploitation of natural resources associated with growing population has led to increasing pollution, declining water quality, land degradation and other environmental problems. Within such circumstances climate change represents an additional stress which has multiple consequences such as extreme climate events including flood, draughts, heat wave, cold stream, melting of Himalayan glaciers and so forth. Due to such events agricultural productivity is suffering from severe losses and attainment of food security is under tremendous threats. The signs of such changes already felt may become more prominent over next couple of decades. If this time is not utilized properly it may be too late to avoid many foreseen bitter consequences. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 38-45